A manganese-based precursor material, a method for preparing the same and applications thereof
Patent Information
- Application Number
- CN202611221138.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-08-12
AI Technical Summary
[0003]现有技术在高纯度硫酸锰和Mn3O4的制备方面取得了一定进展,但仍面临产品粒度和形貌难以控制等问题
1、本发明采用电池回收所产生的含锰废液为原料来制备锰基前驱体材料,不仅实现了材料的回收利用,而且能够有效避免电池废料对环境所带来的污染。配合具有特殊组成的第一沉淀剂和第二沉淀剂,可将电池回收所产生含锰废液中的Fe、Ca和Al的含量控制在10ppm以下,Cu和Zn的含量控制在5ppm以下,从而获得高纯度的含锰溶液,为制备高纯度且具有窄粒度分布的电池级锰基材料提供良好基础。
Smart Images

Figure CN122725359B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of battery materials technology, specifically relating to a manganese-based precursor material, its preparation method, and its application. Background Technology
[0002] With the rapid development of new energy technologies, manganese-based materials are increasingly widely used in the field of lithium-ion battery cathode materials. Battery-grade manganese sulfate, as one of the important raw materials for preparing manganese-based materials, has attracted much attention regarding its preparation process. In the preparation of battery-grade manganese sulfate, the manganese-containing solution first needs to be purified to remove impurity ions such as Fe, Ca, Cu, Zn, and Al. Common purification methods include P204 extraction, P507 extraction, sodium fluoride precipitation, and ammonium bicarbonate precipitation. For example, P204 extraction can effectively remove impurities such as Fe, Al, and Ca, while sodium fluoride is used to remove calcium ions. By controlling the pH value, temperature, and reaction conditions, the purification effect can be further improved. The purified solution is usually processed into a high-purity manganese sulfate solution through crystallization, precipitation, or back-extraction. Furthermore, by controlling parameters such as crystallization time and mother liquor retention ratio, the purity and yield of the product can be further improved. In the preparation of Mn3O4, a two-step precipitation-oxidation method is typically used. First, manganese sulfate solution is reacted with ammonia to generate Mn(OH)₂ precipitate, which is then converted to Mn₃O₄ through oxidation. During this process, the particle size and morphology of the product are controlled by adjusting parameters such as reaction temperature, pH, and type of oxidant. Finally, by adjusting the pH and oxidation conditions, Mn(OH)₂ can be converted into composite materials such as MnOOH@Mn₃O₄ and Mn₃O₄@Mn₃O₄, which can serve as precursors for lithium-ion battery cathode materials. For example, LiMn₂O₄ or LiFe₁-xMn₄ with excellent electrochemical performance can be prepared through oxidation and dehydration in air. x PO4 material.
[0003] Existing technologies have made some progress in the preparation of high-purity manganese sulfate and Mn3O4, but problems such as difficulty in controlling product particle size and morphology still exist. For example, in the preparation of Mn3O4, although the traditional precipitation oxidation method can obtain products with a certain particle size, its particle size distribution width (Span = (D...)) is limited. 90 -D 10 ) / D 50 The range is relatively wide, making precise control difficult. Furthermore, the lack of effective nucleating agents or control methods results in poor product uniformity and dispersibility. Summary of the Invention
[0004] To address the shortcomings of the existing technologies, this invention provides a manganese-based precursor material, its preparation method, and its applications. The technical solution of this invention utilizes nano-Mn3O4 as magnetic particles, sodium hydroxide and ammonia as precipitants, and combines magnetic field control and pH adjustment to achieve precise control over the precipitation of Mn(OH)2-coated Mn3O4. This results in the preparation of high-purity precursor powder with controllable particle size, opening up new avenues for the preparation of cathode materials for lithium-ion batteries.
[0005] To achieve the above objectives, the technical solution adopted by the present invention is to provide a method for preparing a manganese-based precursor material, comprising the following steps: S1: The manganese-containing wastewater generated from battery recycling is treated to remove impurities, ensuring that the contents of Fe, Ca, and Al in the manganese-containing wastewater are below 10 ppm, and the contents of Cu and Zn are below 5 ppm, to obtain purified manganese solution; the manganese-containing wastewater comprises the following components by mass percentage: Mn 2+ 10.0~13.0 w / %, Na + <0.025w / %, Ca 2+ <0.05w / %, K + <0.01w / %, Zn 2+ <0.003 w / %, Fe <0.002 w / %, Cu 2+ <0.001w / %, Al 3+ <0.002 w / %, trace metals ≤0.001 w / %; trace metals are at least one of Co, Ni, Pb, Cd and Cr; S2: Add magnetic nano Mn3O4 particles to purified manganese solution, disperse by ultrasonication, apply an alternating magnetic field, start stirring simultaneously, and add a third precipitant under the alternating magnetic field and stirring conditions. React at 50~70℃ for 60~180min to obtain a precipitate of Mn(OH)2 coated with Mn3O4; the third precipitant is at least one of sodium hydroxide solution and ammonia water. S3: Adjust the pH of the system obtained after the S2 reaction to 10-11, then continuously introduce oxygen-containing gas and oxidize at 50-70℃ for 120-180 min, then filter, collect the solid product, and obtain the precursor. S4: Heat the precursor to 300~400℃ in air atmosphere and calcine for 60~90 minutes to obtain manganese-based precursor material.
[0006] Based on the above technical solution, the present invention can be further improved as follows.
[0007] Furthermore, the removal of impurities from the manganese-containing waste liquid in S1 includes the following steps: S11: Add a first precipitant for precipitating Fe / Cu / Zn impurities to the manganese-containing waste liquid under stirring and at 40~60℃, and adjust the pH of the system to 4.5~5.0, and keep it at the temperature and stir until the amount of precipitation no longer increases; the first precipitant is at least one of barium sulfide and ammonium fluoride; S12: Maintain stirring and system temperature, add a second precipitant for precipitating Ca / Al impurities, and adjust the pH of the system to 3.0~4.0. Keep stirring at the temperature until the amount of precipitate no longer increases; the second precipitant is at least one of oxalic acid and sodium carbonate. S13: Filtration, collection of filtrate, and obtaining purified manganese solution.
[0008] Furthermore, the first precipitant is a mixture of barium sulfide and ammonium fluoride, with the mass ratio of barium sulfide to Fe / Cu / Zn being 18~22:1 and the mass ratio of ammonium fluoride to Fe / Cu / Zn being 1.8~2.2:1; the second precipitant is a mixture of oxalic acid and sodium carbonate, with the amount of oxalic acid added based on an oxalic acid concentration of 0.1~0.2 mol / L in the system and the amount of sodium carbonate added based on a sodium carbonate concentration of 0.05~0.1 mol / L in the system.
[0009] This invention employs a first precipitant and a second precipitant for impurity removal, and the precipitation reactions involved are all based on ion concentration and K. sp The difference in solubility product and coordination / hydrolysis equilibrium allows the target impurities to be converted into sparingly soluble solids under the action of the selected precipitant and removed by magnetic field or filtration, thereby achieving the preparation of high-purity manganese-based precursors. The specific reaction is as follows: Barium sulfide (BaS) is slightly soluble in water, releasing sulfur. 2- Ions (BaS→Ba) 2+ +S 2- ), S 2- with Fe 2+ / Fe 3+ Cu 2+ Zn 2+ Formation of metal sulfides with extremely low solubility: Fe 2+ +S 2- →FeS↓、2Fe 3+ +3S 2- →2FeS↓+S↓; Cu 2+ +S 2- →CuS↓;Zn 2+ +S 2- →ZnS↓; These sulfides K sp (10) -20 ~10 -30The concentration of Fe, Cu, and Zn is much lower than that of metal ions in the solution, thus causing rapid precipitation and achieving the removal of Fe, Cu, and Zn.
[0010] Ammonium fluoride (NH4F) is a strong electrolyte and provides F. - With NH4 + Under acidic or weakly alkaline conditions, F - with Fe 3+ Al 3+ Formation of the coordination anion [FeF6] 3- [AlF6] 3- Subsequently with NH4 + They combine to form an insoluble salt: 3NH4 + +[FeF6] 3- →[NH4]3[FeF6]↓; 3NH4 + +[AlF6] 3- →[NH4]3[AlF6]↓; F - It can also be combined with Cu 2+ Zn 2+ Generate CuF2, ZnF2 (K sp ≈10 -6 ~10 -7 At appropriate pH and concentration, these ions will also precipitate, further reducing the residual concentration of Fe / Cu / Zn. Therefore, NH4F captures these metal ions through fluoride precipitation (Fe and Al are hexafluoro complexes, while Cu and Zn are difluorides).
[0011] Oxalic acid dissociates in water to produce C2O4. 2- Ca 2+ With C2O4 2- It forms calcium oxalate CaC₂O₄·H₂O, which has extremely low solubility (K₂O). sp ≈10 -9 Al precipitates rapidly under acidic-neutral conditions. 3+ It can also react with C2O4 2- This forms aluminum oxalate Al2(C2O4)3·nH2O, which also has very low solubility, leading to Al... 3+ It is solidified and removed with the sediment (see the general principle of oxalate precipitation).
[0012] Na2CO3 dissociates to provide CO3. 2- Ca 2+ +CO3 2- →CaCO3↓, CaCO3's K sp ≈2.8×10 -9 It is far lower than the Ca content in the system.2+ The concentration was so high that a white precipitate was immediately formed after the addition of Na2CO3 and was then filtered out. Al 3+ With CO3 2- The directly formed Al2(CO3)3 is unstable and easily hydrolyzes to form aluminum hydroxide Al(OH)3↓ (Al 3+ +3CO3 2- +3H₂O→Al(OH)₃↓+3HCO₃ - The hydroxide is also difficult to dissolve, thus completing the removal of Al.
[0013] Furthermore, the D of magnetic nano-Mn3O4 particles 50 The particle size is 20~50nm; the added magnetic nano Mn3O4 particles react with the Mn in the purified manganese solution. 2+ The mass ratio is 1:1 to 1000.
[0014] Mn3O4 has a spinel structure, Mn 2+ Located at tetrahedral sites, Mn 3+ Located at octahedral sites, this structure is similar to the lattice of subsequently formed hydroxides such as Mn(OH)₂ and MnOOH, which can reduce the interfacial energy for nucleation and promote the "heterogeneous nucleation growth" process. Simultaneously, the nanoscale structure gives Mn₃O₄ particles an extremely large specific surface area, providing ample heterogeneous interfaces for Mn₃O₄ nucleation. 2+ →Mn(OH)2 precipitates on its surface, thereby significantly increasing the nucleation density and inhibiting particle aggregation.
[0015] Furthermore, the applied alternating magnetic field has an intensity of 0.1~0.5T and a frequency of 20~200kHz.
[0016] Under the influence of an alternating magnetic field (20~200kHz), magnetic Mn3O4 nanoparticles are driven by alternating magnetic torque, resulting in rapid tumbling and drifting motions. The higher the magnetic field frequency, the faster the switching speed of the magnetic force, leading to an increase in the instantaneous acceleration and rotational speed of the particles, resulting in a significant increase in the kinetic energy of the particles in the liquid phase. This increased kinetic energy leads to a greater relative velocity between particles in the same volume of liquid, thus increasing the probability of collisions. High-frequency magnetic fields can also create weak magnetic field gradients locally, causing particles to aggregate and disperse more frequently in space, further increasing the number of collisions.
[0017] Furthermore, the stirring speed in S2 is 200~400 r / min.
[0018] Furthermore, the concentration of sodium hydroxide solution in S2 is 1~2 mol / L, and the concentration of ammonia water is 1~2 mol / L; the third precipitant is added dropwise at a rate of 0.5~2 L / min.
[0019] Mn 2+ Mn(OH)2 precipitates with NaOH / ammonia. The lattice defects and high-energy surfaces on the surface of Mn3O4 particles provide low-energy heterogeneous nucleation sites, allowing Mn(OH)2 to be deposited on their surface first, forming a core-shell structure of Mn(OH)2 coating Mn3O4.
[0020] In traditional precipitation processes, increased supersaturation in the solution triggers extensive secondary nucleation, generating numerous small new nuclei and resulting in a wide particle size distribution. Under the influence of an alternating magnetic field, as the collision frequency increases, existing Mn(OH)₂-coated Mn₃O₄ particles (i.e., "nucleating agents") more readily capture Mn from the solution. 2+ With OH - This promotes the continued deposition of material on existing nuclei rather than the formation of new nuclei. This collision-deposition-dominated growth pattern significantly reduces the rate of secondary nucleation, fundamentally inhibiting the generation of fine new grains.
[0021] Because secondary nucleation is suppressed, the main particle growth path in the system shifts to "continued growth of existing nuclei" rather than the rapid generation of new nuclei. Particles achieve more uniform deposition within the same time window, resulting in a more concentrated particle size distribution and a significantly narrower particle size distribution width (Span) in the final product.
[0022] Furthermore, the oxygen-containing gas in S3 is an oxygen atmosphere with a purity of ≥99%.
[0023] The present invention also discloses a manganese-based precursor material, which is prepared by the above-described preparation method.
[0024] The present invention also discloses the application of the above-mentioned manganese-based precursor material in the preparation of lithium-ion batteries.
[0025] The beneficial effects of this invention are: 1. This invention uses manganese-containing wastewater generated from battery recycling as a raw material to prepare manganese-based precursor materials. This not only achieves material recycling but also effectively avoids environmental pollution caused by battery waste. By using a first and second precipitant with specific compositions, the content of Fe, Ca, and Al in the manganese-containing wastewater generated from battery recycling can be controlled below 10 ppm, and the content of Cu and Zn can be controlled below 5 ppm, thereby obtaining a high-purity manganese-containing solution. This provides a good foundation for preparing high-purity battery-grade manganese-based materials with a narrow particle size distribution.
[0026] 2. This invention addresses the long-standing industry pain points in traditional manganese-based precursor preparation processes, such as wide particle size distribution, poor particle size uniformity, and difficulty in precisely controlling morphology. By introducing nano-Mn3O4 magnetic particles as nucleating agents and using an alternating magnetic field with parameters ranging from 0.1 to 0.5T and 20 to 200 kHz, a novel growth mechanism of "magnetically driven tumbling - global collision - heterogeneous deposition" is constructed. This fundamentally overcomes the bottleneck of irregular secondary nucleation that is difficult to avoid in traditional precipitation oxidation processes, and enables the stable mass production of high-purity manganese-based precursors with narrow particle size distribution.
[0027] 3. This invention provides directional motion energy to the nano-magnetic nucleating agent through an alternating magnetic field, driving the nucleating agent to continuously tumble and drift within the entire reaction vessel. This completely solves the problem of local agglomeration caused by insufficient natural diffusion of the nucleating agent in traditional processes. All Mn(OH)2 precursors simultaneously complete heterogeneous coating growth on the surface of the pre-dispersed nucleating agent, completely suppressing randomly generated free micronuclei. As a result, the particle size distribution of the final material is extremely concentrated, which can meet the stringent requirements of downstream lithium battery cathode materials for precursor particle size consistency.
[0028] 4. After obtaining the core-shell structure of Mn(OH)2 coated with Mn3O4, this invention achieves the controllable oxidation and dehydration of Mn(OH)2 by adjusting conditions such as pH, temperature, and atmosphere, thereby achieving the goal of controllable product morphology and particle size. Attached Figure Description
[0029] Figure 1 This is a particle size distribution diagram of the manganese-based precursor material obtained in Example 1; Figure 2 This is a particle size distribution diagram of the manganese-based precursor material obtained in Example 2; Figure 3 This is a particle size distribution diagram of the manganese-based precursor material obtained in Example 3; Figure 4 This is a particle size distribution diagram of the manganese-based precursor material obtained in Comparative Example 1; Figure 5 This is a particle size distribution diagram of the manganese-based precursor material obtained in Comparative Example 2; Figure 6 The particle size distribution diagram is shown for the manganese-based precursor material obtained in Comparative Example 3. Detailed Implementation
[0030] The specific embodiments of the present invention will be described in detail below with reference to examples.
[0031] Example 1
[0032] A manganese-based precursor material is prepared by the following steps: (1) The manganese-containing waste liquid generated from battery recycling is transferred into a jacketed acid-resistant stainless steel reactor. The composition and mass percentage of the manganese-containing waste liquid are as follows: Mn(Mn 2+ 12.0 w / %, Na + 0.02w / %, Ca 2+ 0.04w / %, K + 0.008w / %, Zn 2+ 0.002 w / %, Fe(Fe 2+ / Fe 3+ 0.0015 w / %, Cu 2+ 0.0008w / %, Al 3+ 0.0015 w / %, total content of other trace metals (Co, Ni, Pb, Cd, Cr, etc.) 0.0008 w / %.
[0033] Start the stirrer and control the stirring speed at 300 r / min. Stabilize the system temperature at 55℃ by introducing a heat transfer medium through the jacket. Then add the first precipitant for precipitating Fe / Cu / Zn impurities. The first precipitant is a mixture of barium sulfide and ammonium fluoride. The mass ratio of added barium sulfide to the total mass of Fe / Cu / Zn is 20:1, and the mass ratio of added ammonium fluoride to the total mass of Fe / Cu / Zn is 2:1. Adjust the pH of the system to 4.8, and keep it at the temperature while stirring until the amount of precipitation no longer increases. The Fe, Cu, and Zn impurities in the system form insoluble sulfide and fluoride complex salts that precipitate. A second precipitant, a mixture of oxalic acid and sodium carbonate, was added to precipitate Ca / Al impurities. The amount of oxalic acid added was based on a concentration of 0.15 mol / L in the system, and the amount of sodium carbonate added was based on a concentration of 0.075 mol / L. The pH of the system was adjusted to 4.5, and the mixture was kept warm and stirred until the amount of precipitation no longer increased, and the Ca and Al impurities in the system were fully precipitated as calcium oxalate, calcium carbonate, and aluminum hydroxide. The solution was then filtered through a 0.5 μm ceramic membrane filter, and the filtrate was collected to obtain purified manganese solution. Analysis showed that the contents of Fe, Ca, and Al in the purified manganese solution were less than 10 ppm, and the contents of Cu and Zn were less than 5 ppm.
[0034] (2) The purified manganese sulfate solution was transferred into a reactor equipped with an alternating magnetic field generator, and magnetic nano-Mn3O4 particles (D) were added to the reactor. 50 Using 30nm particles as nucleating agents, the reaction of magnetic Mn3O4 nanoparticles with Mn in manganese sulfate solution was controlled. 2+The ion mass ratio was 1:1000. First, the system was pre-treated with an ultrasonic device at a frequency of 40 kHz for 35 minutes to initially disperse the magnetic Mn3O4 nanoparticles in the manganese sulfate solution. Then, an alternating magnetic field generator was activated, and the alternating magnetic field strength was stabilized at 0.3 T and the frequency at 110 kHz, driving the magnetic Mn3O4 nanoparticles to continuously tumble and drift in the manganese sulfate solution.
[0035] (3) While maintaining the above alternating magnetic field parameters unchanged, start the stirring device of the reactor and control the stirring speed to 300 r / min; then add the third precipitant by dripping (dropping rate is 1 L / min). The third precipitant is a mixture of sodium hydroxide solution and ammonia water. The concentration of sodium hydroxide in the mixture is 1.5 mol / L and the concentration of ammonia water is 0.5 mol / L. The amount of the third precipitant added is based on the molar ratio of hydroxide ions to manganese ions in the system being approximately 2.1:1. Simultaneously control the reaction temperature of the system to 60℃ and keep it at the temperature for stirring for 120 min. During the reaction, magnetic Mn3O4 particles are used as nucleating agents to obtain Mn(OH)2 coated Mn3O4 precipitate.
[0036] (4) Transfer the system obtained in step (3) to an oxidation reactor equipped with a gas distributor, continuously introduce an O2 atmosphere with a purity of ≥99% at a flow rate of 3.6 L / min, control the pH of the system to be stable at 10.8 and the temperature to be stable at 60℃, and keep it at the temperature for 150 min to complete the controlled oxidation and dehydration of the surface Mn(OH)2 to obtain the precursor product MnOOH@Mn3O4; then filter and collect the solid product.
[0037] (5) The collected solid product was placed in a muffle furnace, heated to 350°C in air atmosphere and kept at that temperature for 75 minutes. After natural cooling, the manganese-based precursor material Mn3O4@Mn3O4 was obtained.
[0038] Example 2
[0039] A manganese-based precursor material is prepared by the following steps: (1) The manganese-containing waste liquid generated from battery recycling is transferred into a jacketed acid-resistant stainless steel reactor. The composition and mass percentage of the manganese-containing waste liquid are as follows: Mn(Mn 2+ 11.0 w / %, Na + 0.022w / %, Ca 2+ 0.045w / %, K + 0.009w / %, Zn 2+ 0.0025 w / %, Fe(Fe 2+ / Fe 3+ 0.0018 w / %, Cu2+ 0.0009w / %, Al 3+ 0.0018 w / %, total content of other trace metals (Co, Ni, Pb, Cd, Cr, etc.) 0.0009 w / %.
[0040] Start the stirrer and control the stirring speed at 200 r / min. Stabilize the system temperature at 50℃ by introducing a heat transfer medium through the jacket. Then add the first precipitant for precipitating Fe / Cu / Zn impurities. The first precipitant is a mixture of barium sulfide and ammonium fluoride. The mass ratio of added barium sulfide to the total mass of Fe / Cu / Zn is 18:1, and the mass ratio of added ammonium fluoride to the total mass of Fe / Cu / Zn is 1.8:1. Adjust the pH of the system to 4.5, and keep it at the temperature while stirring until the amount of precipitation no longer increases. The Fe, Cu, and Zn impurities in the system form insoluble sulfide and fluoride complex salts that precipitate. A second precipitant, a mixture of oxalic acid and sodium carbonate, was added to precipitate Ca / Al impurities. The amount of oxalic acid added was based on a concentration of 0.1 mol / L in the system, and the amount of sodium carbonate added was based on a concentration of 0.05 mol / L. The pH of the system was adjusted to 4.2, and the mixture was kept warm and stirred until the amount of precipitation no longer increased, and the Ca and Al impurities in the system were fully precipitated as calcium oxalate, calcium carbonate, and aluminum hydroxide. The solution was then filtered through a 0.5 μm ceramic membrane filter, and the filtrate was collected to obtain purified manganese solution. Analysis showed that the content of Fe, Ca, and Al in the purified manganese solution was less than 10 ppm, and the content of Cu and Zn was less than 5 ppm.
[0041] (2) The purified manganese sulfate solution was transferred into a reactor equipped with an alternating magnetic field generator, and magnetic nano-Mn3O4 particles (D) were added to the reactor. 50 Using 20nm particles as nucleating agents, the reaction of magnetic Mn3O4 nanoparticles with Mn in manganese sulfate solution was controlled. 2+ The ion mass ratio was 1:100. First, the system was pre-treated with an ultrasonic device at a frequency of 40 kHz for 30 minutes to initially disperse the magnetic Mn3O4 nanoparticles in the manganese sulfate solution. Then, an alternating magnetic field generator was activated, and the alternating magnetic field strength was stabilized at 0.1 T and the frequency at 20 kHz, driving the magnetic Mn3O4 nanoparticles to continuously tumble and drift in the manganese sulfate solution.
[0042] (3) While maintaining the above alternating magnetic field parameters unchanged, start the stirring device of the reactor and control the stirring speed to 200 r / min; then add the third precipitant by dropping (dropping rate is 0.5 L / min). The third precipitant is a sodium hydroxide solution with a concentration of 1 mol / L. The amount of the third precipitant added is based on the molar ratio of hydroxide ions to manganese ions in the system being approximately 2.1:1; simultaneously control the reaction temperature of the system to 50℃ and keep the reaction at this temperature for 60 min; during the reaction, magnetic Mn3O4 particles are used as nucleating agents to obtain a precipitate of Mn(OH)2 coated with Mn3O4.
[0043] (4) Transfer the system obtained in step (3) to an oxidation reactor equipped with a gas distributor, continuously introduce an O2 atmosphere with a purity of ≥99% at a flow rate of 1.2 L / min, control the pH of the system to be stable at 10.5 and the temperature to be stable at 55℃, and keep it at the temperature for 120 min to complete the controlled oxidation and dehydration of the surface Mn(OH)2 to obtain the precursor product MnOOH@Mn3O4; then filter and collect the solid product.
[0044] (5) The collected solid product was placed in a muffle furnace, heated to 300°C in air atmosphere and kept at that temperature for 60 minutes. After natural cooling, the manganese-based precursor material Mn3O4@Mn3O4 was obtained.
[0045] Example 3
[0046] A manganese-based precursor material is prepared by the following steps: (1) The manganese-containing waste liquid generated from battery recycling is transferred into a jacketed acid-resistant stainless steel reactor. The composition and mass percentage of the manganese-containing waste liquid are as follows: Mn(Mn 2+ 13.0 w / %, Na + 0.024w / %, Ca 2+ 0.048w / %, K + 0.0095w / %, Zn 2+ 0.0028 w / %, Fe(Fe 2+ / Fe 3+ 0.0019w / %, Cu 2+ 0.00095w / %, Al 3+ 0.0019 w / %, total content of other trace metals (Co, Ni, Pb, Cd, Cr, etc.) 0.00095 w / %.
[0047] Start the stirrer and control the stirring speed at 400 r / min. Stabilize the system temperature at 60℃ by introducing a heat transfer medium through the jacket. Then add the first precipitant for precipitating Fe / Cu / Zn impurities. The first precipitant is a mixture of barium sulfide and ammonium fluoride. The mass ratio of added barium sulfide to the total mass of Fe / Cu / Zn is 22:1, and the mass ratio of added ammonium fluoride to the total mass of Fe / Cu / Zn is 2.2:1. Adjust the pH of the system to 5.0, and keep it at the temperature while stirring until the amount of precipitation no longer increases. The Fe, Cu, and Zn impurities in the system form insoluble sulfide and fluoride complex salts that precipitate. A second precipitant, a mixture of oxalic acid and sodium carbonate, was added to precipitate Ca / Al impurities. The amount of oxalic acid added was based on a concentration of 0.2 mol / L in the system, and the amount of sodium carbonate added was based on a concentration of 0.1 mol / L. The pH of the system was adjusted to 5.0, and the mixture was kept at a constant temperature and stirred until the amount of precipitate no longer increased, and the Ca and Al impurities in the system were fully precipitated as calcium oxalate, calcium carbonate, and aluminum hydroxide. The solution was then filtered through a 0.5 μm ceramic membrane filter, and the filtrate was collected to obtain purified manganese solution. Analysis showed that the contents of Fe, Ca, and Al in the purified manganese solution were less than 10 ppm, and the contents of Cu and Zn were less than 5 ppm.
[0048] (2) The purified manganese sulfate solution was transferred into a reactor equipped with an alternating magnetic field generator, and magnetic nano-Mn3O4 particles (D) were added to the reactor. 50 Using 50nm particles as nucleating agents, the reaction of magnetic Mn3O4 nanoparticles with Mn in manganese sulfate solution was controlled. 2+ The ion mass ratio was 1:10. First, the system was pre-treated with an ultrasonic device at a frequency of 40 kHz for 40 minutes to initially disperse the magnetic Mn3O4 nanoparticles in the manganese sulfate solution. Then, an alternating magnetic field generator was activated, and the alternating magnetic field strength was stabilized at 0.5 T and the frequency at 200 kHz to drive the magnetic Mn3O4 nanoparticles to continuously tumble and drift in the manganese sulfate solution.
[0049] (3) While maintaining the above alternating magnetic field parameters unchanged, start the stirring device of the reactor and control the stirring speed to 400 r / min; then add the third precipitant by dripping (dropping rate is 2 L / min). The third precipitant is ammonia water with a concentration of 2 mol / L. The amount of the third precipitant added is based on the molar ratio of hydroxide ions to manganese ions in the system being approximately 2.1:1; simultaneously control the reaction temperature of the system to 70℃ and keep the reaction stirred for 180 min; during the reaction, magnetic Mn3O4 particles are used as nucleating agents to obtain Mn(OH)2 coated Mn3O4 precipitate.
[0050] (4) Transfer the system obtained in step (3) to an oxidation reactor equipped with a gas distributor, continuously introduce an O2 atmosphere with a purity of ≥99% at a flow rate of 9.6 L / min, control the pH of the system to be stable at 11.0 and the temperature to be stable at 70℃, and keep it at the temperature for 180 min to complete the controlled oxidation and dehydration of the surface Mn(OH)2 to obtain the precursor product MnOOH@Mn3O4; then filter and collect the solid product.
[0051] (5) The collected solid product was placed in a muffle furnace, heated to 400°C in air atmosphere and kept at that temperature for 90 min. After natural cooling, the manganese-based precursor material Mn3O4@Mn3O4 was obtained.
[0052] Comparative Example 1 A manganese-based precursor material, whose preparation process is the same as that of Example 1, except that no alternating magnetic field is applied in steps (2) and (3), and the rest of the operation is the same as that of Example 1.
[0053] Comparative Example 2 A manganese-based precursor material, the preparation process of which is the same as that of Example 1, is as follows: the magnetic field strength of the alternating magnetic field applied in steps (2) and (3) is adjusted to 0.05T and the frequency is adjusted to 10kHz. At the same time, the stirring speed in step (3) is adjusted to 100r / min and the calcination temperature in step (5) is adjusted to 480℃. The remaining operations are the same as those of Example 1.
[0054] Comparative Example 3 A manganese-based precursor material, the preparation process of which is the same as that of Example 1, the magnetic field strength of the alternating magnetic field applied in steps (2) and (3) is adjusted to 0.04T and the frequency is adjusted to 10kHz. At the same time, the dropping speed of the third precipitant in step (3) is adjusted to 3L / min and the pH value in step (4) is adjusted to 9.
[0055] Experimental Example The particle size distribution of the manganese-based precursor materials prepared in the above examples and comparative examples was detected using a BT-9300ST laser particle size analyzer. The particle size distribution diagrams of the manganese-based precursor materials obtained in Examples 1-3 are shown below. Figures 1-3 As shown, the particle size distribution diagrams of the manganese-based precursor materials obtained in Comparative Examples 1-3 are respectively as follows: Figures 4-6 As shown in Table 1, the typical particle size distribution of each manganese-based precursor material is shown in Table 2, and the core particle size parameters are shown in Table 2.
[0056] Table 1 Typical particle size distribution of manganese-based precursor materials
[0057] Table 2 Core particle size parameters of manganese-based precursor materials
[0058] The particle size distribution width (Span) of each manganese-based precursor material is calculated using the following formula: Span=(D 90 -D 10 ) / D 50 The particle size distribution calculation results of each manganese-based precursor material are shown in Table 3.
[0059] Table 3 Particle size distribution of manganese-based precursor materials
[0060] from Figures 1-3 As shown in Tables 1-3, the Span of the manganese-based precursor material prepared in Example 1 is only 2.16, with a highly concentrated distribution across the entire particle size range. 90% of the particles are smaller than 4.7 μm, and there are no large aggregates larger than 6.5 μm. This result corresponds to the optimal alternating magnetic field parameters of 0.3 T and 110 kHz, which can stably drive 30 nm Mn3O4 magnetic particles to continuously tumble and drift in solution, significantly improving the interaction between the nucleating agent and Mn in the liquid phase. 2+ OH - The collision probability is high, which makes the growth process of all particles highly synchronized, and secondary nucleation is completely suppressed. In the end, all Mn(OH)2 completes heterogeneous deposition growth on the surface of the existing nucleating agent, resulting in a product with highly uniform particle size.
[0061] The Span of the manganese-based precursor material prepared in Example 2 is 2.23, indicating that even under a low-parameter magnetic field of 0.1T and 20kHz, it can still effectively drive the 20nm nanonucleating agent to complete global dispersion, avoid local nucleating agent agglomeration, and ultimately achieve narrow distribution control of product particle size.
[0062] The manganese-based precursor material prepared in Example 3 has a Span of 2.34, and its particle size distribution curve has the sharpest peak among the three examples. Ultrafine particles smaller than 0.5 μm account for only 1.06%, and large particles larger than 5 μm account for only 7.24%. The particle size distribution is extremely concentrated across the entire particle size range, with 92.76% of the particles distributed within the extremely narrow range of 0.5–5 μm. This is because the high-frequency, high-intensity alternating magnetic field provides extremely high kinetic energy for the large-size nano-Mn3O4, and the tumbling and drifting efficiency of the nucleating agent reaches its peak throughout the reactor, effectively avoiding the risk of local nucleating agent agglomeration. All Mn(OH)2 deposition and growth paths are highly uniform.
[0063] The particle size distribution curves of the manganese-based precursor materials prepared in Examples 1-3 all exhibit a sharp single peak, without obvious double peaks or tailing phenomena, indicating that a large number of free fine new nuclei are not generated in the system. The "collision-deposition" dominant growth mode proposed in this application is fully effective, fundamentally solving the inherent defect of wide particle size distribution in traditional processes.
[0064] The Span of the manganese-based precursor material prepared in Comparative Example 1 reached 6.33, nearly three times that of Example 1. This is because, without an alternating magnetic field to provide driving force, the nano-Mn3O4 nucleating agent, relying solely on natural diffusion, could not be uniformly dispersed in the solution. A large number of nucleating agents agglomerated locally, and simultaneously, the local supersaturation of the solution rapidly increased, spontaneously generating a large number of irregularly nascent Mn(OH)2 micronuclei. These nascent micronuclei lacked a unified growth starting point, and the growth time of different particles varied greatly, ultimately resulting in a mixture of coarse and fine particles. 90 The particle size increased directly to 17.59 μm, far exceeding the level of less than 5 μm in the example group, indicating that the overall particle size distribution was out of control.
[0065] The Span of the manganese-based precursor material prepared in Comparative Example 2 reached 6.73. The magnetic field strength of this group was only 0.05T and the frequency was only 10kHz, far below the protection thresholds of 0.1~0.5T and 20~200kHz in the examples. The alternating magnetic field could not provide sufficient kinetic energy for the nanomagnetic particles, failing to achieve the design goal of global tumbling and dispersion of the nucleating agent. The problems of local enrichment of the nucleating agent and uncontrolled secondary nucleation still existed. Simultaneously, the low stirring rate of 100r / min and the ultra-high calcination temperature of 480℃ further intensified the adhesion and thermal agglomeration between particles, ultimately leading to a further increase in the particle size distribution width. 90 It reached 21.13 μm, which is 4.5 times that of Example 1.
[0066] The Span of the manganese-based precursor material prepared in Comparative Example 3 reached 7.439, making it the sample with the widest particle size distribution among all groups. This group not only had magnetic field parameters (0.04T, 10kHz) below the effective threshold, but also suffered from multiple unfavorable conditions, including a precipitation pH of only 9 and a high precipitant drop rate of 3L / min. The excessively low reaction pH could not provide a stable environment for the uniform coating of Mn(OH)₂, and the excessively rapid precipitant drop rate instantly increased the overall supersaturation of the system, directly triggering a large number of random homogeneous nucleations. The final product contained a large number of immature ultrafine particles around 0.8μm, medium-sized coated particles, and ultra-large aggregates exceeding 30μm. The measured D... 97 With a particle size of up to 30.48 μm, the range of particle size distribution is stretched to its limit.
[0067] Although specific embodiments of the present invention have been described in detail with reference to examples, they should not be construed as limiting the scope of protection of this patent. Various modifications and variations that can be made by those skilled in the art without inventive effort within the scope described in the claims are still within the scope of protection of this patent.
Claims
1. A method for preparing a manganese-based precursor material, characterized in that, Includes the following steps: S1: Remove impurities from the manganese-containing waste liquid generated from battery recycling to reduce the content of Fe, Ca, and Al in the manganese-containing waste liquid to less than 10 ppm and the content of Cu and Zn to less than 5 ppm, thus obtaining purified manganese liquid; The removal of impurities from manganese-containing wastewater includes the following steps: S11: Add a first precipitant for precipitating Fe / Cu / Zn impurities to the manganese-containing waste liquid under stirring and at 40~60℃, and adjust the pH of the system to 4.5~5.0, and keep it at the temperature and stir until the amount of precipitation no longer increases; the first precipitant is at least one of barium sulfide and ammonium fluoride; S12: Maintain stirring and system temperature, add a second precipitant for precipitating Ca / Al impurities, and adjust the pH of the system to 3.0~4.
0. Keep the system warm and stir until the amount of precipitate no longer increases; the second precipitant is at least one of oxalic acid and sodium carbonate; S13: Filtration, collection of filtrate, and obtaining purified manganese solution; The manganese-containing waste liquid comprises the following components by mass percentage: Mn 2+ 10.0~13.0 wt / %, Na + <0.025wt / %, Ca 2+ <0.05wt / %, K + <0.01wt / %, Zn 2+ <0.003wt / %, Fe<0.002wt / %, Cu 2+ <0.001wt / %, Al 3+ <0.002wt / %, trace metals ≤0.001wt / %; the trace metals are at least one of Co, Ni, Pb, Cd and Cr; S2: Magnetic nano-Mn3O4 particles are added to purified manganese solution, ultrasonically dispersed, and then an alternating magnetic field is applied while stirring is started simultaneously. A third precipitant is added under the alternating magnetic field and stirring conditions, and the reaction is carried out at 50-70℃ for 60-180 min to obtain a precipitate of Mn(OH)2 coated with Mn3O4; the D of the magnetic nano-Mn3O4 particles... 50 The particle size is 20~50nm; the added magnetic nano Mn3O4 particles react with the Mn in the purified manganese solution. 2+ The mass ratio is 1:1 to 1000; the third precipitant is at least one of sodium hydroxide solution and ammonia water; the applied alternating magnetic field strength is 0.1 to 0.5 T, and the frequency is 20 to 200 kHz; S3: Adjust the pH of the system obtained after the S2 reaction to 10-11, then continuously introduce oxygen-containing gas and keep it at 50-70℃ for 120-180 min for oxidation, then filter, collect the solid product, and obtain precursor one; S4: Heat the precursor to 300~400℃ in air atmosphere and calcine for 60~90 minutes to obtain the manganese-based precursor material.
2. The preparation method according to claim 1, characterized in that: The first precipitant is a mixture of barium sulfide and ammonium fluoride, wherein the mass ratio of barium sulfide to Fe / Cu / Zn is 18~22:1, and the mass ratio of ammonium fluoride to Fe / Cu / Zn is 1.8~2.2:1; the second precipitant is a mixture of oxalic acid and sodium carbonate, wherein the amount of oxalic acid added is based on an oxalic acid concentration of 0.1~0.2 mol / L in the system, and the amount of sodium carbonate added is based on a sodium carbonate concentration of 0.05~0.1 mol / L in the system.
3. The preparation method according to claim 1, characterized in that: The stirring speed in S2 is 200~400 r / min.
4. The preparation method according to claim 1, characterized in that: The concentration of the sodium hydroxide solution in S2 is 1~2 mol / L, and the concentration of the ammonia solution is 1~2 mol / L; the third precipitant is added by dropping, with a dropping rate of 0.5~2 L / min.
5. The preparation method according to claim 1, characterized in that: The oxygen-containing gas mentioned in S3 is an oxygen atmosphere with a purity of ≥99%.
6. A manganese-based precursor material, characterized in that: It is prepared by the preparation method according to any one of claims 1 to 5.
7. The application of the manganese-based precursor material according to claim 6, characterized in that: The manganese-based precursor material is used to prepare lithium-ion batteries.
Citation Information
Patent Citations
Preparation method of carbon composite manganese-based magnetic material
CN104495940A
Quaternary positive electrode precursor and preparation method and application thereof
CN115286051A
